Characteristics features of maintenance of aircraft gas-turbine engine in the sphear of commercial work of aircraft enterprise - Тарасенко A. B. (Proceedings of National Aviation University (archive), 1998)
Considered is the expediency of creation of region analytic centers for attending the aircraft engines on the basis of automatic systems of control and evaluation of their technical condition accordingly to flight information